Do cattle determine elephant distribution in the Red Volta Valley of northern Ghana? - Sam, Moses; Haizel, Charles; Barnes, Richard (Pachyderm, 2002)
Elephants in the northeastern Ghana border area adjacent Burkina Faso move along the Red Volta River Valley raiding crops enroute, and routinely cross back and forth between the countries. As much of the valley area is forest reserve land, in places up to 14 kms wide, elephant can readily retreat into this refuge after raiding farmers fields. Data collected in the 1999 planting season were used to test the hypothesis that elephant density was inversely proportional to cattle density. The authors developed a multivariate model to explain elephant distribution. Having controlled for other variables, results show that increasing numbers of cattle, indicated by the presence of dung, reduce the probablility of finding elephants outside the forest reserve. The authors suggest 'that cattle grazing could be manipulated to reduce the risk of crop raiding by elephants.